The growth of the Italian economy, 1820-1960 - Cohen, Jon S. (New studies in economic and social history., 2001)
"This volume examines Italy's transformation from a largely rural state in the nineteenth century to today's industrial powerhouse. At the time of unification in 1861, much of the country was backward, poor and agrarian: few would have believed that a hundred years later Italy would become one of the seven largest industrial countries, its people among the wealthiest in the world. This process of development and structural change has generated an enormous and evolving literature, alive with controversies and compelling insights. New research and reinterpretation of existing data have led to a re-evaluation of the nature of Italian dualism, while revisions to national income accounts are modifying the traditional picture of economic growth